1995
DOI: 10.1051/alr:1995002
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Mediterranean reef fish assemblage. Comparisons of population distributions between depths in protected and unprotected areas over one decade

Abstract: Diffcrcnces in Mediterranean fish communities of two rocky coastal arcas, one inside an integral marine reserve and thc second outside the reserve, ncar Banyuls-sur-Mer, France, wcrc compared using underwater visual census aftcr a 12-year interval. In 1980, thc community structure in and outside the marine reserve was studied at two depths (Bell, 1983). In 1992, WC uscd the same methodology to asscss if variations occurred in this fish coinmunity between these two samplings. In both 1980 and 1992, water depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 6 publications
4
94
0
3
Order By: Relevance
“…The differences in abundance and species richness among sites de tected by UVC in the present study are similar to those reported in previous studies for Cerbère-Banyuls MPA (Bell 1983, Dufour et al 1995, Harmelin-Vivien et al 2008. Abundance was lower at OR-N than at NO due to artisanal and recreational fishing pressures at OR-N, in contrast to NO where they are prohibited (Bell 1983, Dufour et al 1995.…”
Section: Suitability Of Dov For Studying Reserve Effectsupporting
confidence: 89%
See 1 more Smart Citation
“…The differences in abundance and species richness among sites de tected by UVC in the present study are similar to those reported in previous studies for Cerbère-Banyuls MPA (Bell 1983, Dufour et al 1995, Harmelin-Vivien et al 2008. Abundance was lower at OR-N than at NO due to artisanal and recreational fishing pressures at OR-N, in contrast to NO where they are prohibited (Bell 1983, Dufour et al 1995.…”
Section: Suitability Of Dov For Studying Reserve Effectsupporting
confidence: 89%
“…Fish assemblage abundance and the species richness stemming from both methods were compared regarding the reserve effect. The present study was carried out at the Cerbère-Banyuls marine reserve (France, Mediterranean Sea), which is known to have an effective reserve effect (Bell 1983, Dufour et al 1995, Harmelin-Vivien et al 2008, Claudet et al 2011. To compare UVC to DOV, a cost-benefit analysis was carried out for each method.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in species composition and abundances among the island sectors were thus substantially modelled by the habitat-and depth-related preferences of fishes. Both depth and habitat type have been frequently demonstrated to play an important role in structuring the Mediterranean nearshore fish assemblages (Dufour et al 1995;Reñones et al 1997;Guidetti 2000;García-Charton & Pérez-Ruzafa 2001;Letourneur et al 2003;Tunesi et al 2006b). …”
Section: Fish Assemblage Composition and Structurementioning
confidence: 99%
“…In fact, a large body of literature has been focused on the effect of protection on fish assemblage structure (for reviews, see Roberts & Polunin 1991;Bohnsack 1998;Halpern 2003). Several investigations carried out along the Mediterranean coasts of France (Francour 1994;Dufour et al 1995;Harmelin et al 1995;Claudet et al 2006), Spain (García-Rubies & Zabala 1990;García-Charton et al 2004) and Italy (La Mesa & Vacchi 1999;Guidetti et al 2005;Cecchi et al 2007) indicated that abundance, biomass and mean size of exploited fish populations were higher within well-enforced marine reserves than in nearby non-protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…Halpern angiver i sit manuskript ni videnskabelige artikler (Alcala 1988;Alcala and Russ 1990;Russ and Alcala 1989;1996;1998a,b;Bennett and Atwood 1991;Dufour et al 1995;Edgar and Barret 1999), der beskriver effekten af lukkede områder ud fra et BACI-design. En naermere analyse af disse artikler med det formål at se, om konklusionerne i artiklerne er den samme som Halperns konklusion ud fra en meta-analyse, er derfor gennemført.…”
Section: Høj Fisketaethedunclassified